Strategi Perencanaan PAUD Berdasarkan Permendikbud No. 137 Tahun 2014 Di PAUD Gemilang Kota Palangka Raya - Lia, Gebi; Julianti, Seri Hartati; Syakema, Lisda Paskalin; Tekerop, Ema Papuana; Colina, Yoan (AUDIENSI: Jurnal Pendidikan dan Perkembangan Anak, 2024)
This study aims to examine the PAUD (Early Childhood Education) planning strategy implemented in PAUD Gemilang, Palangka Raya City, in accordance with the Regulation of the Minister of Education and Culture (Permendikbud) No. 137 of 2014. The method used in this study is qualitative with a phenomenological approach. Data collection was carried out through direct observation, interviews, and documentation. PAUD Gemilang, which was established in 2014 and managed by the Harati Foundation, is a private kindergarten educational institution located on Jalan Bukit Raya, Palangka Raya City. The research findings show that the planning strategy in PAUD Gemilang includes the preparation of work programs for the short, medium, and long term, as well as the provision of adequate facilities and infrastructure to support learning. The implementation of this strategy aims to realize the vision and mission of PAUD Gemilang in providing quality education services for early childhood.